Choice making in Rett syndrome: a descriptive study using video data. Issue 7 (27th March 2018) - Urbanowicz, Anna; Ciccone, Natalie; Girdler, Sonya; Leonard, Helen; Downs, Jenny
Abstract: Purpose: To describe the choice-making abilities of girls and women with Rett syndrome. Method: Females with Rett syndrome registered with the Australian Rett Syndrome Database with a pathogenic MECP2 mutation were included in this study. Video clips showing choice making in 64 females at a median age of 11.6 years (range 2.3–35.6 years) were analysed. Video clips were coded for the location and nature of the choice-making interaction, and the actions of the communication partner and female with Rett syndrome. Results: The majority (82.8%, 53/64) of females made a choice, most using eye gaze. Just under half (24/53) used one modality to communicate their choice, 52.8% used two modalities and one used three modalities. Of those who made a choice, 50% did so within 8 s. The length of time to make a choice did not appear to vary with age. During choice making, 57.8% (37/64) of communication partners used language and gestures, 39.1% (25/64) used only language and two used language, gestures and symbols within the interaction. Conclusions: The provision of adequate time allowing for a response and observation for the use of multiple modalities could promote effective choice making in females with Rett syndrome. Implications for Rehabilitation: The provision of adequate time allowing for a response will promote effective choice making in girls and women with Rett syndrome. Although almost all girls and women with Rett syndrome used eye gaze to indicate their choice, communication partners also need to recognise and respond to other communication modalities that are sometimes used like body movements.